Immunology of biodegradable nanoparticles: a brief overview on a wide growing field - Anissa Pisani (Open Exploration Publishing Inc., 2021)
Immunity is continuously evolving by evolutionary mechanisms shaped by pathogenic stimuli of different kinds. Man-made nanomaterials (NMs) have been developed in the last decades and represent a novel challenge for our immune system, especially when applied to medical science. Toxicological studies of such nanoparticles (NPs) revealed that size, shape, and surface chemistry are key parameters to understand their noxious effects on cellular mechanisms. Less is known on the immune reactions to NMs since prolonged exposure data are not so detailed as the results for acute administration. The importance of immunity to biocompatible NPs is underlined by their increasing use as drug or gene delivery carriers in common pharmaceutical preparations and vaccines. In the latter case, the immunomodulatory properties of NMs allow their use also as efficient adjuvants to enhance the innate immune response. In the current manuscript, the authors discuss the main concepts in this fast-growing field by restricting our view to NMs with consolidated application in biomedicine.